Electropolymerized poly(3-methylthiophene) onto high density vertically aligned carbon nanotubes directly grown on aluminum substrate: Application to electrochemical capacitors. (1st August 2020) - Vignal, Thomas; Banet, Philippe; Pinault, Mathieu; Lafourcade, Romain; Descarpentries, Jérémie; Darchy, Léa; Hauf, Harald; Reynaud, Cécile; Mayne-L'Hermite, Martine; Aubert, Pierre-Henri
Abstract: Potentiostatic pulsed deposition of poly(3-methylthiophene) (P3MT) is carried out on vertically aligned carbon nanotubes directly grown on aluminum foil (VACNT/Al) in a mixture of ionic liquid in acetonitrile (25/75 v/v) as electrolyte to prepare pseudo-capacitive materials for electrochemical capacitors. VACNT with high density (2.10 11 VACNT/cm 2 ) and anisotropy, have high specific surface area (340 m 2 /g) and serve as template electrode to nanostructure the P3MT coating. The effect of the polymer weight in the nanocomposite on the morphology and electrochemical properties of nanocomposite electrodes is investigated. Up to 70% of P3MT is electrodeposited inside the carpet onto the VACNTs as evidenced by Scanning Electronic Microscopy (SEM) and Energy Dispersive X-Ray Spectroscopy (EDX). A specific capacitance of 170F/g was obtained for the optimal nanocomposite composition (70%). The calculated areal capacitance is 380 mF/cm 2 and the volumetric capacitance is 76 F/cm 3 . In addition, nanostructured electrodes present an excellent stability and capacitance retention after 19, 000 cycles. Finally, asymmetric electrochemical capacitors were assembled and specific energy of 52 Wh/kg (14 Wh/L) and a specific power of 10 kW/kg were obtained. A comparison with EDLC symmetric device highlights the role of P3MT to improve energy while maintaining a high power due to fast diffusion in the channels perpendicularly oriented to the substrate. Graphical abstract: Image 1